Using Nutrient Solution Instead of Fertilizer to Grow Bok Choy (Brassica chinensis) in Thu Dau Mot City - Trung Thanh, Dang; Huynh Anh Tuyet, Nguyen (VNU Journal of Science: Earth and Environmental Sciences, 2025)
Vegetables are an indispensable food in every family's daily meals because of their nutritional ingredients for the human body. The objective of the study is to evaluate the possibility of growing Bok choy in pots in Thu Dau Mot city and determine the appropriate nutrient concentration for vegetables grown in the spring crop from January to March 2024. Research method includes: i) Preparation of nutrient solution to grow vegetables; and ii) Growing Bok choy and evaluating their growth: using nutrient solution from experiment 1 to grow with 6 treatments: NT1 to NT6 (where NT1 is the control and NT2 to NT6 correspond to nutrient concentrations of 1,200, 1,300, 1,400, 1,500 and 1,600 ppm). The results show that the highest yield of Bok choy was 25.2 ton/ha/crop, which was achieved at NT4 using the nutrient concentration of 1,400 ppm, and the lowest yield was at NT1 with 24.9 ton/ha/crop. Research suggests that nutrient concentrations at 1,400 ppm are suitable for Bok choy cultivation. The nutrient solutions show the potential to commercialize in the urban areas and serve as a reference for gardeners who use automatic methods of providing nutrients to plants through a drip irrigation system, saving water, fertilizer and reducing labor.